Indonesia's Soft Power Diplomacy in the Russia-Ukraine War - Dedy Kurmawan Jaya, Mohamad; Pramono, Budi; Eko Hadi Sancoko, Rizerius; wilopo, wilopo (CV. AFDIFAL MAJU BERKAH, 2025)
The Russian-Ukrainian conflict is a prolonged conflict that began during the Cold War between the Western bloc, in this case NATO led by the United States, and the Eastern bloc, namely the Warsaw Pact led by the Soviet Union. In 1999, during the reign of President Gorbachev in the Soviet Union, a political revolution called Glasnots and Peretroika occurred which resulted in the division of the Soviet Union into the Russian State and several small countries that separated themselves. Ukraine as a free country to cooperate in security with the Western bloc, to protect its country from Russian influence. In addition, there are minority groups in Luhansk and Donest who are ethnic Russians who want to join Russia. This prompted Russia to launch a special operation which was followed by a full-scale operation in Ukraine. The purpose of this study is to analyze Indonesia's soft power diplomacy in the Russia-Ukraine conflict. This study uses a qualitative research method with a descriptive approach, according to Sugiyono (2022), the descriptive qualitative research method is a study based on the philosophy of postpositivism used to examine the conditions of natural objects where researchers are key instruments. The results of the study show that the conflict between Russia and Ukraine is a conflict of interest between large countries that want to expand their influence to other countries. Indonesia's diplomatic efforts in the Russia-Ukraine conflict began with President Joko Widodo communicating directly with Ukrainian President Zelensky and Russian President Putin to resolve the conflict between the two countries and inviting them to attend the G20 meeting. Indonesia's role as the holder of the presidency and host of the G20 Summit in 2022. In organizing the G20 in 2022, geopolitical conditions and the global security crisis are among the issues discussed. Therefore, the conflict between Russia and Ukraine automatically becomes a topic of discussion.